MEREKONTRUKSI HUKUM HINDU DALAM REVOLUSI INDUSTRI 4.0 - I Putu Gede Parmajaya (PARIKSA: Jurnal Hukum Agama Hindu, 2019)
In the life of social stratification of Hindu people in Bali in the lead of social life and life is more based on the tradition (event). Although the Hindu in the lives of life always rests on tradition, but still refers to the highest source of Sruti. Sruti as the highest law in Hinduism remains a reference, although in the reality of Hindu people behave based on ethics (Susila) and Ritual (Upakara). If thoroughly examined, then the customs or traditions inherited hereditary by a generation to another among Hindus especially in Bali is actually more regarded as the viewpoint of society that regulates Manners, organizing the relationship of community members in a customary village in socialization in a limited area and having similarities in characteristic and behavior (village of Adat/village of Manners). Let us reorganize the existence of indigenous villages through the laws governing the customary village in organizing and cultivating social behavior of society based on the laws that have been established in the form of Traditions (Awig) as laws and laws that have been able to Ethical behavior in the conduct of the daily life in the community.